2021
DOI: 10.1016/j.envres.2021.111355
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure assessment in outdoor hospitality venues across 11 European countries

Abstract: Objective Due to partial or poorly enforced restrictions secondhand tobacco smoke (SHS) is still present in outdoor hospitality venues in many European countries. This study aimed to assess SHS concentrations in outdoor hospitality venues across Europe and identify contextual exposure determinants. Methods Cross-sectional study. We measured airborne nicotine and evidence of tobacco use in terraces of bars, cafeterias, and pubs from 11 European countries in 2017–2018. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…This result mirrors what has been described in terraces of hospitality venues. 28 Moreover, the increase of older users in smoke-free beaches after the intervention may show a positive effect on a vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…This result mirrors what has been described in terraces of hospitality venues. 28 Moreover, the increase of older users in smoke-free beaches after the intervention may show a positive effect on a vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…These high exposures could be due to the fact that, in Singapore, many open‐air F&B establishments still have smoking sections and designated smoking areas are typically in the form of open‐air areas 36 . Such segregation strategies are, as research has consistently found, ineffective at protecting people from SHS, 2 and may be especially ineffective in densely populated cities where smokers are in close proximity to others 9,17–24 . In New York City, for instance, non‐smokers' nicotine exposures were found to be higher than the national average despite smoking rates in New York City being lower than the national average 29 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Such segregation strategies are, as research has consistently found, ineffective at protecting people from SHS, 2 and may be especially ineffective in densely populated cities where smokers are in close proximity to others. 9,[17][18][19][20][21][22][23][24] In New York City, for instance, non-smokers' nicotine exposures were found to be higher than the national average despite smoking rates in New York City being lower than the national average. 29 This may partly explain why the majority (60%) of our participants reported that they reconsider visiting leisure outlets, such as bars and restaurants, to avoid SHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The precise definition of these open or semiopen spaces has become a key enforcement issue of smoke-free laws in these places because of the difficulties in interpreting and implementing the law around smoking in such outdoor areas. 47 Nicotine and PM 2.5 concentrations in these settings 48 are usually significantly lower than in indoor settings due to air movement and dilution, and there are potentially major differences globally: walking past a smoker on a windswept Scottish beach may lead to considerably lower exposure when compared with sitting next to a group of smokers on a terrace outside on a still, warm evening in a Mediterranean country.…”
Section: Reviewmentioning
confidence: 99%